SISTEM INFORMASI MANAJEMEN SEKOLAH BERBASIS INFORMATION COMMUNICATION TECHNOLOGY (ICT) DALAM PENINGKATKAN MUTU PENDIDIKAN SISWA DI LINGKUNGAN PESANTREN - PRAMUNGKAS, PATREA REOLA (Universitas Nurul Jadid, 2021)
This article analyzes the possible implementation of School Based Management Information System in terms of Information Communication Technologies (ICT) in advancing the quality of educational service for students in islamic boardingschool. This article figures out that pesantren has implemented ICT based Management Information System in order to archieve program of teaching-learning process, to use learning facilities, curriculum, and to increase the teacher professionalism. The planning is implemented by making vision, mission, goals, and strategies in such a way of well structured management. However, there are some obstacles with which pesantren agencies have to deal in implementing this system, such as: limited access of internet and lack of teacher’s experience in using technology of information. Keywords: Management Information System, Information Communication Technology, Quality of Pesantren